ANALISIS REVITALISASI SARANA DAN PRASARANA PASAR TRADISIONAL RAJAWALI KOTA PALANGKARAYA - Vella Vaenasti; Wening Mustikaningsih (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
The research focuses on the analysis of issues related to traditional market facilities and infrastructure, specifically in Rajawali market in Palangka Raya, Central Kalimantan, Indonesia. The study examines the experiences of traditional market traders who have used these facilities within the past five years. Using a theoretical approach, the research finds several problematic aspects. Firstly, the amount of sales space is not an accurate indicator of profitability. Secondly, there is a lack of security facilities for sellers who rent stalls, resulting in additional expenses for stall repairs to ensure safety. Lastly, although certain market facilities are available, they are not being utilized effectively by market consumers, such as parking lots. These findings highlight the need for improvements in the design and management of traditional market facilities and infrastructure to better meet the needs of traders and consumers alike.